A reception analysis of Brgy. Inawayan community on the Coal Fired Power Plant Project - Ceballo, Maicie I.
This study was conducted to identify the reception of Purok Kalapati in Brgy. Inawayan on Coal Fired Power Plant and Coal as an energy source in the region. It looked at the respondents' stand on the aspects of health, environment, economic, and energy source issues, as well as the go involvement, level of acceptance, neutrality, and rejection of people on various concepts presented to them. With the use of the Diffusion of Innovations Framework (Rogers, 1997), the innovation (Coal Fired Power Plant/Coal Power) and attributes which influence the adoption and rejection of such innovation were evaluated. The research revealed that the ego involvement of the community is high. However, on the issues of health and environment they remain neutral. Their opinion ranged from neutral to positive when asked whether they viewed the Coal Fired Power Plant as a huge investment to the community and the region as a whole. This can be attributed to their economic status which, as the demographics reveal, is below average. This study is an addition to the many communication researches using Diffusion of Innovations, and an aid in further understanding community preference on energy options